Methyl methacrylate thermal decomposition: Modeling and laser spectroscopy of species time-histories behind reflected shock waves. (1st March 2023) - Sanders, Isabelle C.; Kuenning, Nicholas M.; Minesi, Nicolas Q.; Pineda, Daniel I.; Spearrin, R. Mitchell
Abstract: The thermal decomposition of methyl methacrylate (MMA) was studied through species time-history measurements of formaldehyde (CH2 O), carbon monoxide (CO), and carbon dioxide (CO2 ) behind reflected shock waves over a temperature range of 1200–1600 K near 1 atm. Tunable laser absorption spectroscopy was employed to spectrally and temporally-resolve a cluster of rovibrational lines in the Q-branches of the v 1 fundamental band and the v 2 + v 4 combination band of CH2 O near 3 . 60 μ m, three rovibrational transitions in the P-branch of the fundamental band of CO near 4 . 98 μ m, and a transition in the R-branch of the ( 0 1 0 0 → 0 1 0 1 ) v 3 band of CO2 near 4 . 19 μ m . Spectral fitting procedures are subsequently used to infer CO, CO2, and CH2 O mole fraction during the pyrolysis of shock-heated mixtures of MMA in argon. These data provided valuable experimental constraints on MMA pyrolysis chemical kinetic models. Sensitivity analysis of a detailed chemical model for MMA decomposition identified specific reactions likely to account for differences observed between the species measurements and simulations of the test conditions. Modified reaction rate parameters for select MMA decomposition reactions are proposed, determined via a genetic algorithm optimization procedure anchored to the speciation data. Highlights: Time-histories of CO, CO2, and CH2 O mole fractions are measured during pyrolysis of shock-heated MMA Reactions most responsible for model disagreement identified by sensitivity analyses New rate constants proposed for decomposition and hydrogen abstraction reactions